The Significance of Natural Sciences in the Formation of Specialists in "Life Safety" - Kuvandikovich, Kuvandikov Oblakul; Turatovich, Usarov Uktam (European Journal of Life Safety and Stability (2660-9630), 2022)
The fundamental ideas and principles of natural science allow students to gain fundamental knowledge about nature and, on their basis, study specialized disciplines of profile training in more detail. Natural and anthropogenic negative physical and chemical factors affecting people are given. The article gives recommendations on selected topics from the courses of physics and chemistry, which need to be studied in depth for better training of specialists in the direction of education "Life Safety".